THE EFFECT OF THE PROBLEM BASED LEARNING (PBL) MODEL WITH POLYA TECHNIQUES ON STUDENTS 'COGNITIVE LEARNING OUTCOMES IN BASIC BUSINESS AND ENERGY MATERIALS IN CLASS X SEMESTER II SENIOR HIGH SCHOOL 1 BATANG KUIS - Yola Heldianty; Togi Tampubolon (ISER (Indonesian Science Education Research), 2020)
This study aims to determine the effect of the problem based learning (PBL) model with the POLYA technique on students' cognitive learning outcomes on the subject matter of business and energy in class X semester II Senior High School Negeri 1 Batang Kuis in 2018/2019 Academic years. This type of research was a quasi experiment with a two group pretest-posttest design. The population of all students of class X Senior High School Negeri 1 Batang Kuis which consists of five classes. The sample selection was done by using cluster random sampling technique. The study involved two classes, namely the experimental class and the control class who were given different treatments. The experimental class and control class each consisted of 30 students. The experimental class was treated with the problem based learning (PBL) model with the POLYA technique and the control class was treated with the conventional learning model. The instrument used in this study was a cognitive learning outcome test in the form of a problem with a total of 8 questions with POLYA's technique scoring guidelines and student activity sheets. The data in this study were analyzed using hypothesis testing t-test. The results showed that there were significant differences, so it can be concluded that there was an effect of using the problem based learning (PBL) model with the POLYA technique on students' cognitive learning outcomes on the subject matter of business and energy in class X Semester II Senior High School Negeri 1 Batang Kuis.